TEMPORARY FOOD STORAGE STANDARS (PARSTOCK) IN THE PASTRY SECTION LABERSA TOBA HOTEL AND CONVENTION CENTRE BALIGE - Septia Warda Ningsih; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This study aims to determine the temporary food storage standars (parstock) in the Pastry Section Labersa Toba Hotel And Convention Centre Balige. This research uses research methods qualitave descriptive and to get the data author uses interview techniques, observation, and documentation. To achieve the standards that have been set, there are several standard storage procedures that must be applied. Among them are appropriate storage space and equipment, appropriate temperature applied, proper preparation method, cleanliness of storage space and equipment, food labeling, appropriate packaging, and sufficient supplies. During the 4 months of conducting research at the Labersa Toba Hotel And Convention Center Balige, it was found that the storage was in good condition but did not meet the correct storage standard procedures. Keywords : Storage Standards, Ingredients, Pastry Section, Hotel